Profile of Pregnant Women who Underwent Cesarean Section and their Perinatal Outcome at a Tertiary Referral Hospital: Profil Ibu Hamil dengan Indikasi Operasi Caesar dan Luaran Perinatal di Rumah Sakit Rujukan Tersier - Junita Indarti; Sigit Purbadi; Ajeng Larasati; Hesti N. Rizqi; Kristian Alda; Adithya Weladatika; Leonita T. A. Sutrisna; Muhammad Azmi; Caesar Nurfiansyah (Indonesian Journal of Obstetrics and Gynecology, 2021)
Abstract Objective: To investigate the effectiveness of referral system, in regard to pregnant women with indication of C-section, and to learn the patients’ profile and their baby’s perinatal outcome.Methods: The research uses a retrospective descriptive method utilizing patient medical records with history of C-section at RSCM from January 2016 to December 2019. The target population is all pregnant women who were referred and performed cesarean section to at the hospital.Results: The most indications of C-section were premature membrane ruptures (16.1%), fetal distress (14.5%) and previous C-section (14.1%). There were 1585 cases (41.9%) coming without referral, 779 cases (20.6%) were bookcase, and 806 (21.3%) non-bookcase without referral. The main reasons for referral were absence of NICU facilities (27.31%), premature membranes rupture (20.81%), and eclampsia/preeclampsia/HELLP syndrome (15.40%). Most babies are born with normal weight (2500-3999 grams) as many as 45.1% and 54.9% are groups of babies with abnormal weight. Most babies have an APGAR score 5 minute of 7-10 (83.6%). As many as 47.8% rooming in and infants requiring perinatological care in both SCN and NICU are 52.1%.Conclusion: The study found that the effectiveness of RSCM tiered referral system still has much room for improvements. The study also found gap between number of referred cases and the cases eventually underwent for C-section with the same indication. The screening can be done better for an indication of the origin of the reference whether it is appropriate to do the reference or not.Keywords: caesarean section, perinatal outcome, pregnant women, referral system. Abstrak Tujuan: Untuk mengetahui efektivitas sistem rujukan pada ibu hamil dengan indikasi seksio sesarea, serta mengetahui profil pasien dan hasil perinatal bayinya.Metode: Studi ini menggunakan metode deskriptif retrospektif dengan memanfaatkan rekam medis pasien riwayat seksio sesarea di RSCM dari Januari 2016 sampai Desember 2019. Populasi sasaran adalah semua ibu hamil yang dirujuk dan dilakukan seksio sesarea di RSCM.Hasil: Indikasi seksio sesarea terbanyak adalah ketuban pecah dini (16,1%), gawat janin (14,5%), dan riwayat seksio sesarea sebelumnya (14,1%). Ada 1.585 kasus (41,9%) yang datang tanpa rujukan, 779 (20,6%) bookcase, dan 806 (21,3%) non-bookcase tanpa rujukan. Alasan utama rujukan adalah tidak adanya fasilitas NICU (27,31%), ketuban pecah dini (20,81%), dan eklampsia/preeklamsia/sindrom HELLP (15,40%). Sebagian besar bayi lahir dengan berat badan normal (2500-3999 gram) sebanyak 45,1% dan 54,9% merupakan kelompok bayi dengan berat badan tidak normal. Sebagian besar bayi memiliki skor APGAR 5 menit 7-10 (83,6%). Sebanyak 47,8% rawat inap dan bayi yang membutuhkan perawatan perinatologi baik di SCN maupun NICU sebanyak 52,1%. Kesimpulan: Studi ini menemukan bahwa efektivitas sistem rujukan berjenjang RSCM masih memiliki banyak ruang untuk perbaikan. Studi ini juga menemukan kesenjangan antara jumlah kasus yang dirujuk dan kasus yang akhirnya menjalani seksio sesarea dengan indikasi yang sama. Penapisan dapat dilakukan lebih baik untuk indikasi asal rujukan apakah layak dilakukan rujukan atau tidak.Kata kunci: ibu hamil, luaran perinatal, seksio sesarea, sistem rujukan